Solve for y (-4+y)/2=6

Math
-4+y2=6
Multiply both sides of the equation by 2.
2⋅-4+y2=2⋅6
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2⋅-4+y2=2⋅6
Rewrite the expression.
-4+y=2⋅6
-4+y=2⋅6
Multiply 2 by 6.
-4+y=12
-4+y=12
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 4 to both sides of the equation.
y=12+4
Add 12 and 4.
y=16
y=16
Solve for y (-4+y)/2=6

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top